Evaluation of the Topical Anti-inflammatory Activity and Antibacterial Activity of Methanol Extract in the Sideroxylon obtusifolium Leaves (2016)
Sideroxylon obtusifolium, known as "quixaba", is used for various medicinal purposes, including in cases of inflammation and bacterial infections, therefore, the study aimed to investigate the topical antibacterial and anti-inflammatory activity of the methanol extract obtained from the leaves of S. obtusifolium. The phytochemical screening of the extract revealed the presence of several classes, including Phenols; Tannins, Flavonoids, catechins and alkaloids. Polyphenols and flavonoids present in this extract were quantified in 150.3 mg of gallic acid equivalents / g extract and 98.5 mg of quercetin equivalents / g extract, respectively. The results obtained by the microdilution tests have shown potential and modulation antibacterial activity when associated gentamicin, and amikacin for multidrug-resistant strains of Staphylococcus aureus. For Escherichia coli, there was synergism for amikacin, gentamicin having antagonism, the same effect was observed forPseudomonas aeruginosa on both antibiotics. In tests for acute models of inflammation by ear edema induced by croton oil, and phenol, the extract had a potent antiedematogenic significant effect (p  0.05). Therefore, the results can be observed biological activities of S. obtusifolium, which is consistent with its use in popular therapy.